Equivalency and Non-equivalency of Lexical Items in English Translations of Nahj al-balagha - Mohammad Javad Moafi (Religious Inquiries, 2015)
Lexical items play a key role in both language in general and translation in particular. Likewise, equivalence is a controversial concept discussed so widely in translation studies. Some theorists deem it to be fundamental in translation theory and define translation in terms of equivalence. The aim of this study is to identify the problems of lexical gaps in two translations of Nahj al-balagha in order to look closely at what possible difficulties translators may undergo. It also seeks to explore the strategies applied accordingly. Some pieces of Nahj al-balagha and two English translations for them are selected, and religious items of the source text and also the strategies applied by the translators to transfer these items are extracted.